Brain metabolic correlates of apathy in amyotrophic lateral sclerosis: An 18F‐FDG‐positron emission tomography stud. (3rd December 2020) - Canosa, Antonio; Vacchiano, Veria; D'Ovidio, Fabrizio; Calvo, Andrea; Moglia, Cristina; Manera, Umberto; Vasta, Rosario; Liguori, Rocco; Arena, Vincenzo; Grassano, Maurizio; Palumbo, Francesca; Peotta, Laura; et al.
Abstract: Background and purpose: The aim of this study was to evaluate brain metabolic correlates of apathy in amyotrophic lateral sclerosis (ALS). Methods: A total of 165 ALS patients underwent 18 F‐2‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography ( 18 F‐FDG‐PET) and Frontal Systems Behaviour Scale (FrSBe) evaluation. FrSBe provides "before" and "after" apathy subscores, referring to premorbid and morbid conditions. "After" apathy subscore and "before‐after" gap, i.e. the difference between "before" and "after" subscores, were regressed against whole‐brain metabolism. Among patients with a pathological "after" apathy subscore (i.e., ≥65), we compared patients with "before" apathy subscores ≥65 and <65, and patients with "before‐after" gaps of <22 and ≥22. Results: In the whole sample, the "after" apathy subscore negatively correlated with metabolism in the dorsolateral prefrontal cortex (DLPFC), dorsomedial prefrontal cortex (DMPFC), ventrolateral prefrontal cortex (VLPFC), premotor cortex (PMC) and anterior cingulate cortex (ACC), and insula bilaterally. A positive correlation was found in the cerebellum and pons. The "before‐after" gap negatively correlated with metabolism in bilateral DLPFC, DMPFC and PMC, and left VLPFC and ACC, and positively correlated with cerebellar and pontine clusters. Among patients with an "after" apathy subscore ≥65, we found no difference between those with "before" apathy subscores ≥65 and <65. Patients with a "before‐after" gap ≥22, compared to patients with a gap <22, showed relative hypometabolism in bilateral DLPFC and DMPFC, and left ACC and PMC, and relative cerebellar and pontine hypermetabolism. Conclusion: No studies on brain 18 F‐2‐fluoro‐2‐deoxy‐D‐glucose positron emission tomography correlates of apathy have been performed in ALS. We found that FrSBe "after" apathy subscore correlated with metabolic changes in brain regions known as neuroanatomical correlates of apathy. Furthermore, our findings support the relevance of the gap between premorbid and morbid conditions to detect behavioural changes due to the neurodegenerative process underlying ALS. Abstract : No studies on brain 18 F‐FDG‐PET correlates of apathy have been performed in amyotrophic lateral sclerosis (ALS). We found that Frontal Systems Behaviour Scale "after" apathy subscore correlated with metabolic changes in brain regions known as neuroanatomical correlates of apathy. Furthermore, our findings support the relevance of the gap between premorbid and morbid conditions to detect behavioural changes due to the neurodegenerative process underlying ALS.